Effect of drying methods on the quality characteristics of dill (Anethum graveolens) greens. (1st February 2016) - Madhava Naidu, M.; Vedashree, M.; Satapathy, Pankaj; Khanum, Hafeeza; Ramsamy, Ravi; Hebbar, H. Umesh
Highlights: Results demonstrated that the LHA is the most preferable drying method for dill greens. Methanolic extracts of dill had a significant effect on scavenging free radicals. Diisoocytl phthalate, Apiol, Phellandrance α-cymene, were the major volatile compounds. Dehydrated dill greens with their constituents can serve as a valuable food additive. Abstract: Different drying methods hot air (HA), 50 °C, 58–63% relative humidity (RH); low humidity air (LHA), 50 °C and 28–30% RH; and radiofrequency (RF), 50 °C, 56–60% RH) were investigated for efficient dehydration of dill ( Anethum graveolens ) greens with optimal retention of color and constituents. The drying for HA and RF was marginally higher (∼22%) compared to HA. Lightness, greenness and yellowness of LHA dried sample were higher than those of the RF and hot-air dried dill greens. Aqueous methanolic extract of dill greens dehydrated by LHA method exhibited higher anti-oxidant activity. Forty-two compounds were identified representing ∼85% of the volatile oil and the major volatile compounds for fresh and dried dill leaf oil were α-Phellandrene, α-cymene, α-pinene, Apiol, 1, 6-Cyclodecodiene, and 1-methyl-5-methylene. Dehydrated dill greens with their constituent polyphenols, carotenoids, ascorbic acid and minerals have been shown good consumer acceptance as well as shelf life and could serve as a valuable food additive to enhance human nutrition.